2018
DOI: 10.15294/ujph.v7i2.20982
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Patients Behavior and Family Health Companion Role on Hypertension Complication Occurrence

Abstract: ABSTRACT Various efforts of hypertension complications prevention have been carried out properly but the prevalence of hypertensive complications in NTT Province is still very high. The study aimed to determine the effect of patient behavior and family health companion role on the incidence of hypertension complications. The study was carried out in the work area of Sikumana Health Center in Kupang City with a case-control design. A total of 40 case samples and 40 control samples were taken by simple-ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…The results also found that drug consumption has a significant relationship with risk factors for complications in hypertension patients (Israfil, 2018). Gymnastic or sports with hypertension patients is an important nursing action in efforts to control hypertension and prevent complications.…”
Section: Resultsmentioning
confidence: 73%
See 3 more Smart Citations
“…The results also found that drug consumption has a significant relationship with risk factors for complications in hypertension patients (Israfil, 2018). Gymnastic or sports with hypertension patients is an important nursing action in efforts to control hypertension and prevent complications.…”
Section: Resultsmentioning
confidence: 73%
“…There are two main nursing diagnoses that are most appropriate for patients at risk of hypertension complications: Risk of Ineffective Mikoard Perfusion Code D0014 and Risk of Cerebral Perfusion Ineffective Code D.0017 which can interfere with myocardial metabolism. This nursing diagnosis is very precise because based on the results of research by Israfil et al, (2018) it was found that 30% of hypertension patients have complications of Coronary Artery Diseases (CAD). These diseases occur in hypertension patients due to ineffective myocardial perfusion.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research on health coaching in families also showed positive results after its implementation; health coaching to improve healthy living behavior, including increasing the patient's physical activity, motivates patients to change their daily behavior for the better (Israfil, 2018). Health coaching also can be used as an effort for clients' and families' health management process and decision-making (Stacey, 2013).…”
Section: Resultsmentioning
confidence: 99%